2017
DOI: 10.3892/ol.2017.7624
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients with soft tissue sarcoma of the chest wall: Analysis of the prognostic significance of microscopic margins

Abstract: Data on prognostic factors and treatment outcomes for chest wall soft tissue sarcomas (STS) are sparse. Wide resections with negative margins are the mainstay of therapy, but the prognostic impact of surgical margins remains controversial. The purpose of the present study was to determine the significance of microscopic margins through a long-term follow-up. The associations between local recurrence-free survival (LRFS), overall survival (OS) and potential prognostic factors were retrospectively assessed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…This finding would provide a more aggressive surgical approach in order to attain wider negative margins. Past studies of our institution which have determined the influence of negative margin widths in STS, in general, could not establish a relationship between margin widths and outcome [24,25]. However, analyses of STS subsets such as angiosarcoma and dermatofibrosarcoma protuberans revealed that margin widths may indeed have an impact on specific entities [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This finding would provide a more aggressive surgical approach in order to attain wider negative margins. Past studies of our institution which have determined the influence of negative margin widths in STS, in general, could not establish a relationship between margin widths and outcome [24,25]. However, analyses of STS subsets such as angiosarcoma and dermatofibrosarcoma protuberans revealed that margin widths may indeed have an impact on specific entities [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, the number of grade 1 tumors was very small, so our analysis was underpowered to detect a significant association between tumor grade and survival. In the six previous studies, the average 5‐year OS rate was 72.5% (range, 57%‐89%). A strength of our study is the inclusion of the greatest percentage of high‐grade sarcoma cases (such as MPNSTs) that has been reported to date.…”
Section: Commentmentioning
confidence: 91%
“…The tumor cells are immunohistochemically positive for vascular markers such as CD31, CD34, ERG, and podoplanin [10]. Surgery is the most common approach to treat angiosarcoma, and achieving surgically negative margins improves prognosis [11,12]. Therefore, accurate evaluation of surgical margins is essential for management of cutaneous angiosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%